Should enhanced resilience be an objective of natural resource management research in developing countries? - Walker, Brian; Sayer, Jeffrey A.; Andrew, Neil L.; Campbell, Bruce M. (Wiley, 2010)
Productivity enhancement has traditionally been the main focus of agricultural research to alleviate poverty and enhance food security of poor farmers in the developing world. Recently, the harmful impact of climate change, economic volatility, and other external shocks on poor farmers has led to concern that resilience should feature alongside productivity as a major objective of research. The applicability of recent work on resilient social–ecological systems to the problems of poor farmers is reviewed, and proposals are made for issues that need to be addressed in determining when and how enhanced resilience might become an objective of research.